Conservation threats from roadkill in the global road network. Issue 11 (10th September 2021) - Grilo, Clara; Borda‐de‐Água, Luis; Beja, Pedro; Goolsby, Eric; Soanes, Kylie; le Roux, Aliza; Koroleva, Elena; Ferreira, Flávio Z.; Gagné, Sara A.; Wang, Yun; González‐Suárez, Manuela
Abstract: Aim: The road network is increasing globally but the consequences of roadkill on the viability of wildlife populations are largely unknown. We provide a framework that allows us to estimate how risk of extinction of local populations increases due to roadkill and to generate a global assessment that identifies which mammalian species are most vulnerable to roadkill and the areas where they occur. Location: Global. Time period: 1995–2015. Major taxa studied: Terrestrial mammals. Methods: We introduce a framework to quantify the effect of roadkill on terrestrial mammals worldwide that includes three steps: (a) compilation of roadkill rates to estimate the fraction of a local population killed on the roads, (b) prediction of population risk of extinction based on observed roadkill rates (for a target group of species of conservation concern and non‐threatened species with high roadkill rates), and (c) global assessment of vulnerability to roadkill for 4, 677 terrestrial mammalian species estimated using phylogenetic regression models that link extinction risk to demographic parameters. Results: We identified four populations among the 70 species in the target group that could become extinct in 50 years if observed roadkill levels persist in the study areas: maned wolf Chrysocyon brachyurus (Brazil), little spotted cat Leopardus tigrinus (Brazil), brown hyena Hyaena brunnea (Southern Africa) and leopard Panthera pardus (North India). The global assessment revealed roadkill as an added risk for 2.7% ( n  = 124) terrestrial mammals, including 83 species Threatened or Near Threatened. We identified regions of concern that have species vulnerable to roadkill with high road densities in areas of South Africa, central and Southeast Asia, and the Andes. Main conclusions: Our framework revealed populations of threatened species that require special attention and can be incorporated into management and planning strategies informing road managers and conservation agencies.